The Cross-Cultural Communications in Business Trips: Statistical Measures in Coordinates of Ukraine - Yaroslav Martynyshyn; Elena Khlystun; Yelena Kovalenko (Communications - Scientific letters of the University of Zilina, 2019)
The purpose of this study is to find ways to increase the effectiveness of cross-cultural communications from the standpoint of Ukrainian business. The methodology of the research is based on statistical measures; there is quantitative identification of parameters of intercultural business communication processes, their modeling, analysis and forecasting. As a result of the study, the relationship between different types of intercultural communication is determined: the transaction oriented and the relationship, formal and informal, monochrome and polychrome, expressive and restrained. Profiles and classifications of the cross-cultural communications have been constructed. The communication disagreements and corresponding reactions of Ukrainian businessmen in different countries and regions of the world have been determined. Models have been developed that reflect the patterns of the relationship between the success of communication (reaction) and intercultural differences. The obtained results can be used to substantiate the cross-cultural communication strategies of business trips.